Who can afford to be critical? : an inquiry into what we can't do alone, as designers, and into what we might be able to do together, as people - Matos, Afonso de, 1998-; Lorusso, Silvio, 1985-; Brown, J. Dakota; D'Aprile, Marianela; Bhatt, Somnath; Aubert, Danielle, 1975-; Fisher, Jack Henrie; Smart, Alan; Mihalko, Greg ([Eindhoven] : Set Margins', 2022)
"Critical Designers' produced by an increasing number of design schools are prompted to address social, political and environmental issues through their practices. Yet, who can afford to continue such effort after graduation? In a dynamic style holding multiple voices, Who Can Afford To Be Critical? discusses the limits that affordability, class and labour impose upon the educational promise of holding a 'critical' practice. Why do we tend to ignore the material and socioeconomic constraints that bind us as designers, claiming instead that we can be powerful agents of change? In fact, where does our agency lie? Instead of focusing on the dream of ethical work under capitalism, could we, instead, focus first on designers' own working conditions, targeting them as one immediate site for collective action? And can we engage politically with the world not necessarily as designers, but as workers, as activists, as citizens?" --Publisher's website (viewed March 9, 2023)
Introduction -- 1. The school is a sandbox and the world outside has nothing to do with it : A. Meetings transcript ; B. No problem: design school as promise (excerpts) / Silvio Lorusso -- 2. I tried to subvert capitalism with my design practice. Now I'm looking for a job. : A. "The subject supposed to recycle" / as explained by Mark Fisher -- B. What we can't do / Afonso Matos ; C. Meetings transcripts ; D. Systemic change' / Afonso Matos -- 3. Framing design as art or as an ontological life force is all fun and games until you have to pay your rent ; A. Meetings transcripts ; B. 6 theses on the deprofessionalization of design / Silvio Lorusso -- C. Typography, automation and the division of labor (excerpts) / J. Dakota Brown -- D. If "labor is entitled to all it creates", where does that leave graphic design? (excerpts) / interview by Somnath Bhatt with Jack Henrie Fisher, Alan Smart, Greg Mihalko and Danielle Aubert -- E. Not everything is 'architecture' (excerpts) / Marianela D'Aprile -- 4. What if designers unionized...? Haha just kidding... Unless...... : A. Meetings transcripts ; B. Politics beyond design / Afonso Matos -- C. What could a union do for graphic design? / mixed materials by Evening Class -- D. About the International Typographical Union (excerpts) / J. Dakota Brown -- Responsibility by the editor.
"Set Margins' #11."--Colophon
Cover title
BIB
Keywords: Art and design -- Study and teaching (Higher); Design; Art -- Political aspects